Wilsons disease and autoimmune liver disease overlap syndrome: a clinical study - R., Ramasubramanian; Y., Jaipaul; Rejoice, Poppy; A., Shafique; Anandan, Heber (International Journal of Research in Medical Sciences, 2019)
Background: The coexistence of Wilson’s disease and autoimmune liver disease in a same patient is a rare entity. Combined treatment with steroid and D-penicillamine may be effective. Aim of the study was analyse the clinical, histological, laboratory profile for patients with chronic liver disease with aim of finding the etiology of the disease. Methods: It is an observational study. Common clinical presentations were evaluated. Laboratory investigations done include complete blood count, renal and liver function tests, prothrombin time, viral markers for hepatitis A, B, C and E, USG abdomen and pelvis, portal Doppler studies and upper GI endoscopy. Specific tests include ANA, AMA, ASMA, Anti LKM-1Ab, serum ceruloplasmin and 24hrs urinary copper were done. Liver biopsy was done in selected patients. Results: Commonest clinical presentation was abdominal distension (80%), abdominal pain (30%), pedal edema (60%), splenomegaly (40%) and upper GI bleed (40%). Laboratory investigation revealed anemia (50%), thrombocytopenia (70%), prothrombin time prolongation in (60%), normal liver function in 60%, abnormal liver function in (40%). Autoimmune markers revealed ANA strong positivity in (40%), mild positivity in (60%). AMA, ASMA, Anti-LKM-1 were negative in all cases (100%). Liver biopsy showed features of autoimmune liver disease and Periportal copper deposition in 80% of cases. Conclusions: Coexistence of Wilson’s disease and autoimmune liver disease is a rare entity and medical treatment with steroids and D-penicillamine simultaneously to be started in these patients.